2016
DOI: 10.1128/cmr.00022-16
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and Prolonged Intravenous β-Lactam Dosing: Implications for the Clinical Laboratory

Abstract: SUMMARYBeta-lactam antibiotics serve as a cornerstone in the management of bacterial infections because of their wide spectrum of activity and low toxicity. Since resistance rates among bacteria are continuously on the rise and the pipeline for new antibiotics does not meet this trend, an optimization of current beta-lactam treatment is needed. This review provides an overview of optimization through use of prolonged- and continuous-infusion dosing strategies compared with more traditional intermittent infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 130 publications
1
48
0
1
Order By: Relevance
“…Since b-lactam antibiotics exhibit time-dependent killing of bacteria, the length of time for which the free drug concentration is above MIC (%T >MIC) correlates well with the killing of bacteria. Pharmacological studies have clearly shown that with prolonged infusion, and even more so with continuous infusion, the %T >MIC increases in blood and in other compartments [61]. In patients with postoperative intracranial infections, better CSF target level attainment of cefepime has been shown with continuous versus intermittent infusion [62].…”
Section: Prolonged or Continuous Antibiotic Administration And Therapmentioning
confidence: 99%
See 1 more Smart Citation
“…Since b-lactam antibiotics exhibit time-dependent killing of bacteria, the length of time for which the free drug concentration is above MIC (%T >MIC) correlates well with the killing of bacteria. Pharmacological studies have clearly shown that with prolonged infusion, and even more so with continuous infusion, the %T >MIC increases in blood and in other compartments [61]. In patients with postoperative intracranial infections, better CSF target level attainment of cefepime has been shown with continuous versus intermittent infusion [62].…”
Section: Prolonged or Continuous Antibiotic Administration And Therapmentioning
confidence: 99%
“…In patients with postoperative intracranial infections, better CSF target level attainment of cefepime has been shown with continuous versus intermittent infusion [62]. Clinical studies have shown inconsistent results for patients with bacteraemia [61]. A systematic review revealed lower mortality for extended or continuous infusion of carbapenems or piperacillin/tazobactam, compared with intermittent infusion, based mostly on observational studies [63].…”
Section: Prolonged or Continuous Antibiotic Administration And Therapmentioning
confidence: 99%
“…While the reliable detection of Pseudomonas aeruginosa by BC detection systems is a top priority for treatment optimization and effective antimicrobial stewardship (13)(14)(15)(16), no studies have evaluated these BC bottle systems for meropenem, ceftolozane-tazobactam, and ceftazidime-avibactam. These potent broad-spectrum ␤-lactams are frequently administered in high doses and with prolonged infusions to optimize their activity (17); therefore, there is an increased likelihood that the time to detection (TTD) will be delayed or that samples will be sterilized. We aimed to investigate the effect of the in vitro neutralization of clinically achievable concentrations of meropenem, ceftolozanetazobactam, and ceftazidime-avibactam on TTDs and growth curves of P. aeruginosa in two widely used BC bottle systems, the Bactec Plus Aerobic Plus/F, and BacT/Alert FA Plus Aerobic bottles.…”
mentioning
confidence: 99%
“…The authors showed that, in order to determine by the bacteriological method the efficacy of antibiotic therapy in patients receiving these antibiotics, it is necessary to take samples for plating right before the administration of the next dose of drugs. Figure 4 shows changes in the concentrations of antibiotics of the beta-lactam group for various methods of administration reviewed by Grupper et al [83]. The review demonstrated the advantage of long-term infusion (3-4 h) of antibiotics compared with short-term administration.…”
Section: Approaches To Assessing Efficacy Of Antibiotic Therapymentioning
confidence: 99%